1991
DOI: 10.1590/s0034-89101991000400007
|View full text |Cite
|
Sign up to set email alerts
|

Desnutrición infantil, coeficiente de desarrollo y su relación con el medio ambiente: un estudio piloto

Abstract: The socio-cultural factors that might be influencing the normal psychomotor development of the undernourished infant are studied. The sample consisted of 32 mother-infant dyads: 16 having normal DQ (Group A) and 16 having a below normal DQ (Group B) according to Bailey's Test applied to infants who entered a Nutritional Recuperation Center. Results showed that there were some differences in the infants' backgrounds: infants of Group A were the product of a wished-for pregnancy (p less than .05), and were separ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
1
1

Year Published

1997
1997
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
0
1
1
1
Order By: Relevance
“…Based on the fact that the sample of children come from poor families with a per capita income of less than half a MW, it can be assumed that most of the children attend public day care centers that do not offer the proper stimulation for child development in a period in which the child is most vulnerable to environmental factors 3,33 . An intriguing result was the observation that longer father-child time was statistically associated with a higher percentage of motor persistence delay, unlike the results of previous studies that show paternal presence as a positive effect on child development 6,7,24 . Bustamante 34 reported that paternal presence is usually related with unemployment and that, by the father's own conception of fatherhood, being a provider is a necessary condition to having an affectionate relationship with his children and excludes physical care, which is attributed to women 34 .…”
Section: Discussioncontrasting
confidence: 66%
See 1 more Smart Citation
“…Based on the fact that the sample of children come from poor families with a per capita income of less than half a MW, it can be assumed that most of the children attend public day care centers that do not offer the proper stimulation for child development in a period in which the child is most vulnerable to environmental factors 3,33 . An intriguing result was the observation that longer father-child time was statistically associated with a higher percentage of motor persistence delay, unlike the results of previous studies that show paternal presence as a positive effect on child development 6,7,24 . Bustamante 34 reported that paternal presence is usually related with unemployment and that, by the father's own conception of fatherhood, being a provider is a necessary condition to having an affectionate relationship with his children and excludes physical care, which is attributed to women 34 .…”
Section: Discussioncontrasting
confidence: 66%
“…Among the factors that influence child development are nutritional and environmental conditions, stimulation which can be aided by the family' s routine, and the family' s cultural, educational and socioeconomic standards [2][3][4][5][6][7] . The factors that have a negative influence on child development are more frequent in the lowincome population due to the effects of low socioeconomic status, poor nutrition and inadequate environmental stimulation 3,4,6 .…”
Section: Introductionmentioning
confidence: 99%
“…: sono noturno agitado ou em menor quantidade). Além disso, possíveis variações nos estímulos ambientais e na interação com a mãe 19 , fatores que não foram controlados neste estudo, podem ter influenciado.…”
Section: Variáveisunclassified